Model indicators of collective interactions of highly qualified football players during the game - V.M. Kostiukevych (H.S. Skovoroda Kharkiv National Pedagogical University, 2019)
The aim of the study wos to determine the model indicators of highly qualified football players in the game based on a comprehensive analysis of competitive activity. Material and methods. The study involved players from 8 leading Ukrainian football teams. A video analysis of 8 football matches of the leading teams of Ukraine was conducted. There was a pedagogical observation of the collective actions of the players. The actions of the players were recorded in a specially developed expert card. The indicators of the quantity and effectiveness of the use of various tactical actions by the players were determined. Collective interactions of football players during the game during ball possession and during the ball were recorded. The number of interactions of 2-3 players, 4-5 players, 7 or more players was determined during possession of the ball and during the selection of the ball. The number of different types of gears (short, medium, long) was also analyzed. Results. An analysis of the competitive activity of club and national teams of high qualification allows us to state that the result of the match largely depends on the collective interactions of the players. The collective interactions of football players during the game are carried out in two phases - possession of the ball and selection of the ball. In the phase of possession, the interaction of 2-3 players is 71.6%, 4-6 players - 24.1%, out of 7 and more players - 4.3%. In the selection phase, the interaction of 2-3 players is 63.1%, 4-6 players - 22.9%, 7 or more players - 14.0%. It was revealed that the number of ball passes during the game, which are divided: in tactical direction - holding (29.8%), developing (55, 4%), aggravating (14.8%); in range - short (58.3%), medium (30.5%), long (30.5%); in range and coordination complexity: in 1 RCS 60.9% of short, 36, 4% of medium, 27.7% of long transfers are performed; in 2 CSWs - 32.7% of short, 49.6% of medium, 27, 7% of long transfers; in 3 CSWs - 6.4% of short, 14% of medium, 15, 8% of long transfers. Conclusions. The most important component of the collective interactions of the players is the ball passes, which are divided into tactical directions by holding (14.8%), developing (55.4%) and sharpening (14.8%).